State Responsibility During Covid-19 Pandemic In The Perspective Of The Indonesian Constitutional Law - Riris Ardhanariswari (Jurnal Dinamika Hukum, 2021)
Abstract--Coronavirus first emerged and spread to humans from Wuhan city, China at the end of December 2019 and spread to Indonesia and became a serious concern in Indonesia since March 2020 as it was stated as a nationaloutbreak. The Indonesian Constitution asserts that the purpose of formation of the State of Indonesia is to protect the whole people of Indonesia and the entire homeland of Indonesia, to promote general prosperity, to develop the nation’s intellectual life, and to contribute to the implementation of a world order based on freedom, lasting peace and social justice. The Covid-19 pandemic is not only occurring in Indonesia, but also in other countries, and each country certainly issues different policies. The state with its authority should respond to the condition in the community, which this research is based on. This research employed a normative legal method and used secondary data as its main data. Various policies are issued by the Indonesia Government from Government Regulation in Lieu of Law No. 1 of 2020 which has become Law No. 2 of 2020, Government Regulation No. 21 of 2020 on the Large Scale Social Restriction in Coronavirus Disease 2019 (COVID‑19) Response Acceleration to technical regulations issued by ministers to solve Covid-19 related issues. The policies are certainly the implementation of the state’s responsibility to the people.Keywords- State Responsibility, Constitutional Law